Analysis of the intrinsic value of life in the context of synthetic biology - Zhang, Yi; Chen, Yuling; Liao, Bohua (Frontiers in Bioengineering and Biotechnology, 2025)
The ongoing advancements in synthetic biology, employing either “bottom-up” or “top-down” approaches to construct synthetic life, are generating significant interest. However, the broad application of these scientific practices remains fraught with ethical controversies. Thus, investigating the intrinsic value associated with synthetic life is crucial for determining whether and how synthetic life should be constructed and utilized. This study draws upon and extends Ronald Sandler’s theory of intrinsic value, analyzing the intrinsic subjective value of synthetic life from the perspectives of ecocentrism, human culture, and the structural properties of synthetic life itself. It examines the intrinsic objective value of synthetic life based on its natural purposes. Additionally, the study explores the inherent worth of synthetic life from three angles: biology, subjectivity, and relationships with human beings. We conclude that the intrinsic value of synthetic life increases sequentially from synthetic microorganisms to synthetic plants, synthetic invertebrates, synthetic vertebrates, and synthetic humans. All forms of synthetic life possess intrinsic subjective and objective value. However, only synthetic life above the grade of synthetic microorganisms has inherent worth; thus, humans have moral obligations towards them.